Evaluation of Semicircular Canal Function by Video Head Impulse Test in Patients With Labyrinthine Fistula Due to Cholesteatoma. Issue 5 (June 2022) - Fujiwara, Keishi; Morita, Shinya; Fukuda, Atsushi; Hoshino, Kimiko; Nakamaru, Yuji; Homma, Akihiro
Abstract : Objectives: To evaluate semicircular canal function in patients with labyrinthine fistula (LF) due to cholesteatoma by the video Head Impulse Test (vHIT). Study Design: Retrospective case review. Setting: Tertiary referral center. Patients: Ten patients with LF due to cholesteatoma and six without LF underwent vestibular examination. Intervention: Diagnostic. Main Outcome Measures: The gain in vestibulo-ocular reflex (VOR) and the presence of catch-up saccade were examined for the semicircular canals in patients with LF. Results: Seven of 10 cases (70.0%) in the fistula group were judged to have semicircular canal dysfunction based on preoperative evaluation. VOR gains in the patients with LF were significantly lower than those in the patients without LF. VOR gain decreased significantly in accordance with the severity of the LF. The postoperative VOR gain more than 6 months after surgery was significantly improved compared with the preoperative VOR gain. Conclusions: The vHIT is thought to be the most suitable method for evaluating semicircular canal function in patients with LF due to cholesteatoma as it is not influenced by middle ear pathology and can evaluate the function of the vertical canals. The vHIT could predict whether a LF is present or not before surgery, and the vHIT is essential for surgery for patients with LF.